Transformation of 21st Century Surau-Based Education - Eka Asih Febriani; Kokom Komalasari; Elly Malihah; Anesito L Custilas (LPPM Universitas PGRI Sumatera Barat, 2023)
Transformation education needs to reorganize, update and adapt the education system in the 21st century This study aims to analyze and describe the transformation of surau-based education in the 21st century in shaping the character of the religious Minang generation in Padang. This research uses social construction theory proposed by Peter L. Berger and Thomas Luckman. The research approach used is qualitative research with the case study method. The determination of informant criteria was carried out by means of purposive sampling. Data obtained through observation, interviews, and documentation. Data were analyzed by following the interactive data analysis model from Miles and Huberman which includes data reduction, data display, and verification or drawing conclusions. The results of the study show surau-based education in the 21st century is packaged in the form of Al-qur’an reading and writing programs at TPQ-TPA, didikkan subuh, wirid remaja, and youth boarding schools. Surau is interpreted today, no longer as it was before the 21st century, namely martial arts, and a place to sleep or where adult men gather but functions the same as a mushala and a mosque, namely a place of worship and learning that are not only for boys but also for girls of school age. The house of worship for Muslims in Padang is used as a means of implementing certified qur’anic educational institutions. The novelty in this research is the internalization of surau-based 21st century education values.